PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMBAR DAN SUARA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS I SEKOLAH DASAR - Sri Ramadhani, Tarisa; Sukirno; Juliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the fact that some first-grade students still experienced difficulties in beginning reading, while the learning media used were still dominated by conventional media that had not been able to optimally support the improvement of reading ability. This study aimed to determine the design, validity, practicality, and effectiveness of an interactive PowerPoint learning medium based on pictures and sound. This research employed the research and development (R&D) method with the ADDIE model, consisting of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were first-grade students of SD Negeri 8 Langsa. The data collection instruments included observation sheets, interviews, validation questionnaires (for material, media, and language experts), teacher and student response questionnaires, and pretest-posttest results. The results showed that the material validation obtained a score of 90% with the criterion "Very Valid", the media expert obtained 98% with the criterion "Very Valid", and the language expert obtained 100% with the criterion "Very Valid". At the implementation stage, the practitioner assessment obtained 100% with the criterion "Very Practical" and the student response obtained 93.25% with the criterion "Very Practical". The trial results showed that the N-gain value of the pretest and posttest results was 0.70 with the criterion "Medium" and the N-gain percentage was 69.55% with the criterion "Quite Effective". The suggestion of this research is that teachers utilise the developed interactive PowerPoint media based on pictures and sound in the learning process.